In vitro characterization and viability of Vero cell lines supplemented with porcine follicular fluid proteins study - Youngsabanant, Mayuva; Rabiab, Suphaphorn; Gumlungpat, Nongnuch; Panyarachun, Busaba (Science, Engineering and Health Studies, 2019)
The purpose of this research was to study the morphological features of cells and test the porcine follicular fluid (pFF) supplements in Vero cell lines culture. The pFF in the estrous cycle was collected and kept sterile properly. The fluid was categorized into three types: small size (1-3 mm), medium size (4-6 mm) and large size (>7 mm) follicles. In the control group, Vero cell lines were cultured in dulbecco's modified eagle medium (DMEM). In the positive control group, Vero cell lines were cultured in DMEM and supplemented using 10% heat-treated fetal bovine serum (HTFBS). In the third group, Vero cell lines were cultured in DMEM and supplemented using pFF from small, medium and large sized ovarian follicles at 2, 4, 20, 40, 200, 400, 500 and 600 μg protein/mL concentrations for 24 h, using MTT assay. The results related to pFF from small-, medium- and large-sized follicles indicated that the percentage of cell viability in tested group at 400-600 µg protein/mL showed the percentage of viability came out to be the highest, significantly than that in the control group (p<0.05), and not different from that in the positive control group. In summary, according to morphological studies, the pFF effectively helped increase the growth of Vero cell lines closely as compared to the cultured group supplemented by HTFBS in the laboratory.